2007
DOI: 10.1016/j.tim.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Actin and Rho GTPases in herpesvirus biology

Abstract: Viruses have evolved a variety of interactions with host cells to create an optimal niche for viral replication, persistence and spread. The actin cytoskeleton of the host cell and actin-regulating Rho GTPase signaling pathways can be involved in several of these interactions. This review focuses on recent findings on herpesvirus interactions with actin and Rho GTPases during viral entry, replication in the nucleus and egress. Unraveling these often fascinating interactions might also provide additional insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 80 publications
3
56
0
5
Order By: Relevance
“…These projections extend to neighboring cells (Fig. 3C) and similar cell projections at late stages of infection have been detected in several a-herpesviruses, such as HSV-1, VZV and PRV enhancing the intercellular viral spread (for review 35,36,39,40 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These projections extend to neighboring cells (Fig. 3C) and similar cell projections at late stages of infection have been detected in several a-herpesviruses, such as HSV-1, VZV and PRV enhancing the intercellular viral spread (for review 35,36,39,40 ).…”
Section: Discussionsupporting
confidence: 77%
“…There is increasing evidence that herpesviruses are capable of usurping Rho GTPases during the main stages of the viral lifecycle, such as virus entry, translocation of the viral particles to the nucleus and viral egress. 35,36 Depending on the endocytic uptake routes engaged during the initial interaction of the herpesviruses with the host, specific Rho GTPase signaling is triggered and significant actin cytoskeleton rearrangements are induced, [37][38][39][40] creating an optimal microenvironment for viral replication, persistence and dissemination. It is of interest that apart from lytic infection, the interactions between gamma-herpeviruses and Rho GTPase signaling remain active even during non-productive infection, facilitating either the establishment of latency 41 or affecting cell motility and invasion and promoting the oncogenic properties of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that herpes simplex and Epstein-Barr viruses activate Rac1 and Cdc42 GTPases to form lamellipodia and filopodia in epithelial cells and fibroblasts (Melamed et al, 1994;Favoreel et al, 2007). Thus, signalling pathways, known to regulate the formation of filopodia, were analysed after DENV-2 binding to HMEC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cells pretreated with blebbistatin, some filopodia were induced by DENV-2, although the filopodia that were formed were unstable. It has been reported that filopodial activity and surfing of murine leukemia virus in host cells depend on actin dynamics and motor activity of myosin II and other non-conventional myosins such as myosin V and myosin X (Lehmann et al, 2005;Favoreel et al, 2007;Ikebe, 2008;Mattila & Lappalainen, 2008). Unfortunately, myosins in HMEC-1 cells have not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the neuropathogenic EHV-1 strain uses the same strategy to infect adjacent cells as the Jan-E EHV-1 (Słońska et al 2014). The literature data suggest that other herpesviruses also induce the formation of similar actin projections -HHV-1 in the Vero cells and BHK, VZV in the HFF cells or SuHV-1 in RK13 and PK15 cells (Favoreel et al 2005(Favoreel et al , 2007.…”
Section: Discussionmentioning
confidence: 99%